Experiences of lay counsellors who provide VCT for PMTCT of HIV and AIDS in the Capricorn district, Limpopo Province - R.N. Malema; D.W. Malaka; T.M. Mothiba (AOSIS, 2009)
Human Immune Deficiency Virus (HIV) and Acquired Immune-Deficiency Syndrome (AIDS) still carry a stigma in the community. Many people do not know their status and they are still reluctant to be tested including pregnant women despite the fact that Voluntary Counselling and Testing (VCT) is offered for free in South Africa. In South Africa VCT for HIV and AIDS is offered by lay counsellors in public hospitals and clinics. The study conducted by Mate, Bennet, Mphatswe, Barker and Rollins (2009:5483) outlined that in South Africa the prevention of mother-to-child transmission (PMTCT) of HIV guidelines have raised hope that the national goal of reducing perinatal HIV transmission rates to less than 5% can be attained. A qualitative, exploratory, descriptive and contextual study was conducted in 15 public clinics of the Polokwane Municipality in the Capricorn District, Limpopo Province. The purpose of the study was to determine the experiences of the lay counsellors who provide VCT for the PMTCT of HIV and AIDS in the Capricorn District, Limpopo Province. Data were collected through one-to-one interviews using a semi-structured guide (De Vos et al, 2006:296). The findings of the study reflected the following: the content of training and counselling skills received by lay counsellors were satisfactory, there was lack of counsellor support and in-service education. A program for in-service education and support for all lay counsellors who have had VCT training should be conceptualised and implemented.